A TRIF-INDEPENDENT BRANCH OF TLR3 SIGNALING - Yamashita, Michifumi (2012)
Double-stranded RNA is a common pathogen-associated molecular pattern that is recognized by cellular Toll-like receptor 3 (TLR3) and used by virus-infected cells to activate specific transcription factors and trigger induction of antiviral genes. Here, we report a new branch of TLR3-signaling that does not lead to gene induction, but affects many cellular properties, such as cell migration, adhesion and proliferation. We demonstrated that the migration of multiple cell lineages was affected by dsRNA-treatment or influenza virus infection, in a TLR3-dependent fashion. Surprisingly, for this effect of TLR3 signaling, the adaptor proteins, TRIF and MyD88, were not required. The effects of the new pathway were mediated by the proto-oncoprotein c-Src, which bound to TLR3 after dsRNA-stimulation of cells. The response was biphasic: upon dsRNA-treatment we observed an immediate increase in cell motility followed by its strong inhibition. Our results indicate that the first phase was mediated by dsRNA-induced phosphorylation and activation of Src whereas the second phase resulted from the sequestration of activated Src in lipid rafts, thus decreasing its active cytoplasmic pool. As expected, two other functions of Src, its effect on cell adhesion and cell proliferation, were also inhibited by dsRNA-treatment. These results demonstrate that activated TLR3 can engage Src to trigger multiple cellular effects and reveal a possible link between innate immune response and cell growth regulation. This study also provides a rare example of TLR-mediated cellular effects that do not require gene induction and the first example of an adaptor-independent effect of any TLR.